IMPLEMENTASI DAN ANALISIS TINGKAT AKURASI SOFTWARE PENYELESAIAN PERSAMAAN NON LINIER DENGAN METODE FIXED POINT ITERATION DAN METODE BISECTION - Asminah Asminah; Vivi Sahfitri (Jurusan Teknik Informatika, 2012)
This study aims to build the software solution of non-linear equations by the method of Bisection and Fixed Point Iteration, revealed that the software non-linear equations have been carried out through five stages, namely: (1) Engineering systems modeling (2) needs analysis software, (3) create a design (4) code generation, (5) conduct testing and implementation using the programming languages C # (C-Sharp). Validator research have 4 experts in the field of both matter and media. Data analysis using descriptive analysis techniques. Settlement of one case of non-linear equations assessed the average time it takes not too long because the turnaround time less than 1 second. Judging from the fault tolerance, the number of iterations and the average time it takes the Bisection method is better than the fixed point iteration method. Overall in terms of both content and media, that any assessment of the software is considered good and decent that can be used lecturers taught courses in numerical methods, specially methods Bisection and Fixed Point iteration.